Effects of Polymethoxylated Flavone Metabolites on ApoB100 Secretion and MTP Activity in Huh7.5 Cells - Gonçalves, Danielle R. [UNESP]; Cesar, Thais B. [UNESP]; Manthey, John A.; Costa, Paulo I. [UNESP] (Bentham Science Publishers, 2022)
Background: Citrus polymethoxylated flavones (PMFs) reduce the synthesis of liver lipoproteins in animal and in vitro cell assays, but few studies have evaluated the direct effects of their metabolites on this highly regulated process. Objective: The aim of the study was to investigate the effects of representative metabolites of PMF on the secretion of liver lipoproteins using the mammalian cell Huh7.5. Methods: In this study, the influences of three PMFs and five previously isolated PMF metabolites on hepatic apoB-100 secretion and microsomal transfer protein (MTP) activity were evaluated. Tangeretin (TAN), nobiletin (NOB) and 3,5,6,7,8,3′,4′-heptamethoxyflavone (HMF), their glucuronides (TAN-Gluc, NOB-Gluc and HMF-Gluc) and oxidatively demethylated metabolites (TAN-OH, NOB-OH, HMF-OH), were incubated with Huh7.5 cells to measure their inhibitory effects on lipid synthesis. Results: The results showed that TAN, HMF and TAN-OH reduced the secretion of apoB-100 in a dose-dependent manner, while NOB and the other tested metabolites showed no inhibition. MTP activity in the Huh7.5 cells was significantly reduced in the presence of low concentrations of TAN and high concentrations of NOB-OH. This study also showed that PMFs and PMF metabolites produced a wide range of effects on apoB-100 secretion and MTP activity. Conclusion: The results suggest that while PMFs and their metabolites control dyslipidemia in vivo, the inhibition of MTP activity cannot be the only pathway influenced by these compounds.
Keywords: demethylated PMF metabolites; glucuronide PMF metabolites; Hepatic lipids; heptamethoxyflavone; nobiletin; tangeretin